PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) DI KANTIN SEKOLAH TERHADAP KEMAMPUAN PENGGUNAAN NILAI MATA UANG PADA SISWA TUNAGRAHITA RINGAN - MERTHADANA, ERLA; MAHMUDAH, SITI (Jurnal Pendidikan Khusus, 2019)
This research was set background by the problem of mentally retardation students in mathematics discipline especially in Rupiah currency value usage which was still less. This research purpose was to prove the influence of Realistic Mathematics Education (RME) approach in school canteen toward the ability of currency usage of mentally retardation students. This research used quantitative approach of pre experiment kind with One group pretest ? posttest design. The result of pre-test average value was 54.19 the students were given 6 times treatment and it was obtained the value result of student RFA got the highest score, student AF got the lowest score indicated by the average value of post-test i.e. 81.07. This research result indicated that there was influence of Realistic Mathematics Education (RME) approach in school canteen toward the ability of currency value usage to mild mentally retardation students. It could be concluded that there was significant influence toward the ability of currency value usage to mild mentally retardation students (T ? Ta, critic value 5%). Keywords: Realistic Mathematics Education (RME), currency value usage, mild mentally retardation.